Synthesizing evidence on nutrition challenges among people living with HIV/AIDS in sub- Saharan Africa: a protocol for a scoping review - Dzinamarira, Tafadzwa; Mashora, Moreblessing Chipo (International Journal Of Community Medicine And Public Health, 2019)
Background: Good nutritional status is highly significant for individuals who are infected with HIV. However, they still face a number of nutritional challenges. The proposed scoping review will map literature on the nutritional challenges facing people living with HIV/AIDS (PLWH) and guide future research in nutritional management to improve health outcomes for PLWH. Here we outline a scoping review protocol designed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols (PRISMA-P 2015 Guidelines). Methods: The Arksey and O’Malley’s 2005 scoping methodological framework further improved by Levac et al. 2010 will guide the search and reporting. Searches will be conducted for eligible articles from MEDLINE (PubMed), MEDLINE, CINAHL, Academic Search Complete and ISI Web of Science (Science Citation Index) electronic databases. Two independent reviewers will conduct the search guided by an inclusion and exclusion criteria. Quality appraisal of the included articles will be conducted guided by the mixed methods appraisal tool 2018 version. We will employ NVivo version 12 for thematic content analysis. Conclusions: The findings of this review will guide future research in nutritional management to improve health outcomes for PLWH in sub-Saharan African. This review will be disseminated electronically in a published peer reviewed article and in print.